Ultrasonography-guided Intervention in the Achilles Tendon and Plantar Fascia - Martin, Silvia; Moriñigo, Javier Gomez (Seminars in Musculoskeletal Radiology, 2023)
Tendinopathy is very common in the foot and ankle. Achilles tendinopathy is a painful overuse injury that often occurs in athletes, especially those who participate in running and jumping sports. Plantar fasciitis is the most frequent cause of plantar pain in the adult heel. Initial treatment of these conditions is conservative. However, in some cases symptoms only improve slowly, and many cases are intractable. When conservative management fails, ultrasonography guided injections are indicated. We discuss the main interventions performed in the foot and ankle for Achilles tendinopathy, retrocalcaneal bursitis, and plantar fasciitis. We describe the different agents that can be used and the various ultrasonography-guided procedures that offer technical and practical information to improve daily clinical practice.
Keywords: ultrasonography-guided procedures; ankle; Achilles tendon; foot; plantar fascia